Undang-Undang Tatacara Mal Mahkamah Syariah- Prinsip dan Amalan - Norman Zakiyy Chow Jen-T'Chiang; Hasnizam Hashim (Universiti Sains Islam Malaysia, 2024)
In principle, civil procedure consists of court rules with the overriding purpose of enabling the court to process a civil case right from the process of commencement of action to its disposal in an efficient and expeditious manner. At this point in time, however, there is a scarcity of publications in Malaysia on the subject of civil procedure (tatacara mal) of the Shariah courts. In comparison, there are sufficient texts on the subject of civil procedure of the civil courts and also on the substantive aspects of Syariah laws. Such a situation demands serious attention especially when Syarie lawyers and undergraduate students enrolled for courses relating to Syariah or Law (or a double-degree programme of Syariah and Law) are in need of a book on civil procedure in the Syariah Court that incorporates the substantive aspects of civil litigation and drafting skills.